Tinjauan Sistem Pendaftaran Rawat Jalan di Puskesmas Kelurahan Klender Tahun 2023 - Rizky Alfiansyah; Puteri Fannya; Daniel Happy Putra; Laela Indawati (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Puskesmas is a functional health organization as well as a center for community health development. The Klender urban health center currently uses an online registration system and offline registration. This study aims to determine the online and offline outpatient registration system at the Klender Village Community Health Center in 2023. This research is a qualitative research. In this study, researchers directly observed the process of outpatient registration. Retrieval of research data is done by observation and interviews with registration officers. The results of the study found that online registration uses the Jaksehat application, patients do not need to come to the health center to register, patients come to the health center to validate queue numbers to the polyclinic only. Calling patients who register online is prioritized with a system of calling queue numbers 1-5, 11-15 and so on. Offline registration is done by having patients come directly to the puskesmas and queue to register. For calling patients, register offline after patients register online with queue numbers 6-10, 16-15, etc. The problems found in registration were the separate queues for patients who registered online and offline and there was a mismatch in calling patients according to the serial number of the queue. The conclusion in this study is that online registration of outpatients uses the Jaksehat application and offline registration is carried out using the system used by the puskesmas. It is expected that the puskesmas will separate the queues of patients who have registered online with patients who have registered offline.